EDUCATION ON THE UTILIZATION OF MORINGA LEAVES DECIL IN INCREASING BREAST MILK PRODUCTION: EDUCATION ON THE UTILIZATION OF MORINGA LEAVES DECIL IN INCREASING BREAST MILK PRODUCTION - Anuhgera, Diah Evawanna; Ritonga, Nikmah Jalilah; Sitorus, Riris; Simarmata, Juni Mariati; Handayani, Dwi (JURNAL PENGMAS KESTRA (JPK), 2022)
thing in the growth and development of babies. Education that utilizes natural plants and has benefits for mothers and babies can be given to the community to help practice increasing breast milk through consumption of Moringa leaves. The aim of this education is to help mothers use Moringa oleifera leaves as a natural ingredient to increase breast milk. The target for this service is breastfeeding mothers using Leaflet media, video tutorials and Moringa leaves. The methods used are lecture, discussion, and PLA (Participatory Learning and Action) methods. The desired output is to increase education in breastfeeding by increasing milk production by consuming Moringa leaves by 20%. Implementation of dedication is given by doing a pretest and posttest. The results of the implementation showed that the average pretest score was 56.4, the posttest average score after education was 79, the average increase in score was 22.6. This shows that education can increase the utilization of Moringa leaves to increase breast milk production by 40%.